2019
DOI: 10.3126/jcmsn.v15i3.25389
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Dexmedetomidine and Fentanyl for Attenuation of Hemodynamic Response to Laryngoscopy and Intubation

Abstract: Background: Laryngoscopy and intubation cause hypertension and tachycardia which can lead to myocardial ischemia or cerebrovascular hemorrhage in patients with raised intracranial pressure, hypertension. The objective of this study was to compare the efficacy of dexmedetomidine (1 mcg/kg) and fentanyl (2 mcg/kg) in attenuating hemodynamic response to laryngoscopy and intubation. Methods: Sixty patients scheduled for elective surgeries under general anaesthesia were randomly divided into two groups: Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Only one study compared fentanyl, dexmedetomidine, and lidocaine [11]. All other studies have compared only fentanyl and dexmedetomidine [12][13][14][15][16][17][18]. In this meta-analysis, lidocaine was ignored, as the aim of this meta-analysis was to compare fentanyl and dexmedetomidine.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one study compared fentanyl, dexmedetomidine, and lidocaine [11]. All other studies have compared only fentanyl and dexmedetomidine [12][13][14][15][16][17][18]. In this meta-analysis, lidocaine was ignored, as the aim of this meta-analysis was to compare fentanyl and dexmedetomidine.…”
Section: Resultsmentioning
confidence: 99%
“…neurosurgical procedure [12], and cardiac surgery [18]. All other studies included all kinds of elective surgical procedures [13][14][15][16][17]. Two reviewers assessed the risk of bias and it was found to be perfectly consistent, which showed that the overall quality of the study was moderate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations